Determining biocide efficacy for treating established sulfate-reducing biofilms using flow cell systems - Okpala, Gloria N.; Walker, Anna L.; Brideau, Craig; Colarusso, Pina; Gieg, Lisa M. (Frontiers in Microbiology, 2026)
Sulfate-reducing microorganisms (SRM) can contribute to souring and to the corrosion of infrastructure built to support many industrial operations, including in aquatic environments. While chemicals such as biocides can effectively treat planktonic cells, less is known about biocide efficacy for treating established biofilms potentially plaguing infrastructure. We used a biofilm flow cell system to examine the efficacy of sodium nitroprusside (SNP, a nitrosating compound proposed as a “green” biocide) and alkyl dimethyl benzyl ammonium chloride (ADBAC), a membrane-disrupting biocide used across many sectors, to mitigate existing SRM biofilms. Biofilms were treated with various amounts of SNP (15–750 ppm) or ADBAC (25–500 ppm) for 10–14 h. Biofilm responses were tracked by measuring sulfide concentrations and were also analyzed for microbial community composition and by microscopy. Planktonic SRM cultures were inhibited by 15 ppm SNP, while biofilms were only transiently inhibited by 15–750 ppm SNP. Planktonic cultures were inhibited by 10 ppm ADBAC, but 50 ppm ADBAC did not suppress sulfide production in existing biofilms. ADBAC added at 100 ppm to the biofilms showed transient inhibition while the 250 and 500 ppm treatments completely inhibited sulfidogenesis. Two-photon microscopy showed primarily viable cells following the 50 ppm ADBAC treatments, a mix of viable and non-viable cells following the 100 ppm ADBAC treatment, and non-viable cells following the 250 and 500 ppm ADBAC treatments, confirmed by quantitative analysis of the images. 16S rRNA gene sequencing showed the prevalence of Desulfobulbus and either Desulfomicrobium or Pseudomonas in active biofilms, with these taxa differentially persisting after many of the biocide treatments. The results revealed that higher doses of biocides are needed to effectively treat existing SRM biofilms compared to planktonic cells, and that biocide dosing may only be transiently effective. Studying the effects of chemical treatments on sessile rather than planktonic communities in aquatic environments may lead to more effective treatment strategies to mitigate problematic biofilms plaguing infrastructure degradation across many industries.